Canada: The Decision to Procure Nuclear Attack Submarines and Its Significance for NATO - Guillory, Theodore (1988)
In June 1987 the Canadian government announced plans to procure 10 to 12 nuclear attack submarines (SSNs). The evidence suggest that, for some Canadians, a primary purpose for this submarine program may not be to enhance the security of NATO, but instead to assert Canada's sovereignty, principally against the United States, in the Arctic region. The thesis discuss this decision and its possible implications for the security of North America and NATO. It is argued that the United States must continue to have unimpeded access to the Arctic region to counter the ever increasing threat posed by Soviet nuclear ballistic missile submarines (SSBNs). Finally the thesis suggests a possible solution to the current sovereignty debate and a potential strategy for employing these SNN to enhance the security of North America and NATO as a whole. Keywords: Naval procurement; Nuclear powered submarine threats; Arctic regions access; Sovereignty; Canada as a naval power; Deterrence; National interests; Theses.